2022
DOI: 10.3390/nano12132184
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Crystalline Silica from Sugarcane Bagasse Ash: Physico-Chemical Properties

Abstract: Sugarcane bagasse South Africa is an agricultural waste that poses many environmental and human health problems. Sugarcane bagasse dumps attract many insects that harm the health of the population and cause many diseases. Sugarcane ash is a naturally renewable source of silica. This study presents for the first time the extraction of nanosilica from sugar cane bagasse ash using L-cysteine hydrochloride monohydrate acid and Tetrapropylammonium Hydroxide. The structural, morphological, and chemical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Thermal properties were investigated using thermogravimetric analysis (TGA) from room temperature to 800°C, reported in [22]. The current study gave insightful information on the thermal characteristics of bagasse ash as shown in Figure 5.…”
Section: Thermal Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Thermal properties were investigated using thermogravimetric analysis (TGA) from room temperature to 800°C, reported in [22]. The current study gave insightful information on the thermal characteristics of bagasse ash as shown in Figure 5.…”
Section: Thermal Analysismentioning
confidence: 96%
“…Figure 5.TGA curves of (a) untreated sugarcane bagasse ash and treated bagasse ash with citric acid. Reproduced with permission from[22], copyright (2022), MDPI.…”
mentioning
confidence: 99%
“…A notable attempt at a green synthesis of crystalline structured silica has been made through a novel synthesis method making use of organic solvents. Seroka et al 41 reported the use of organic chemicals, namely CA and l -cysteine hydrochloride monohydrate ( l -Cys), in the leaching of SCBA, which resulted in crystalline silica with average sizes of 26 nm for CA and 29 nm for l -Cys. Furthermore, tetrapropylammonium hydroxide (TPAH) was utilized as an extraction solvent for further purification by eliminating excess residuals and impurities in the synthesized silica.…”
Section: Green Synthesis Of Silicamentioning
confidence: 99%
“…Because organic acids, alkalis, and solvents can decompose more complex-structured substrates, silica extraction from biomass is one of the most promising methods for green synthesis. One of the most promising methods for the green synthesis of silica and silicon nanoparticles is the chemical and thermal treatment of biomass by replacing toxic reactants and decreasing temperatures [9,10]. Schematic illustration for the production of silica from sugarcane bagasse ash.…”
Section: Green Silica Synthesismentioning
confidence: 99%